2019
DOI: 10.1108/bij-09-2017-0242
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the best practices in green operations strategy of hospitals

Abstract: Purpose The purpose of this paper is to identify the best practices in the green operations strategy of hospitals. Design/methodology/approach A total of 25 cases from all over the world were investigated. The source of data was the annual sustainability reports that were retrieved from Global Reporting Initiative (GRI) database. The present research adopted the benchmarking method and the quantitative content analysis of sustainability reports. Then, the indicative models of best practices were developed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 36 publications
(46 reference statements)
0
22
0
Order By: Relevance
“…The number of clusters developed by this study was four, the number of clusters reported by previous studies, such as Migdadi (2016) and Migdadi and Elzzqaibeh (2018), was three and the number of clusters reported by Migdadi and Omari (2019) was five. In this study, three clusters reported were effective and one was ineffective; this is consistent with the findings of Migdadi and Elzzqaibeh (2018).…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…The number of clusters developed by this study was four, the number of clusters reported by previous studies, such as Migdadi (2016) and Migdadi and Elzzqaibeh (2018), was three and the number of clusters reported by Migdadi and Omari (2019) was five. In this study, three clusters reported were effective and one was ineffective; this is consistent with the findings of Migdadi and Elzzqaibeh (2018).…”
Section: Discussionmentioning
confidence: 50%
“…The lean strategic group scored moderately well in the financial and environmental indicators, and at a lower level in the key performance indicators of operational level. Migdadi and Omari (2019) developed five taxonomies for hospitals: resource management, electrical power management, non-hazard waste, emission-resources management and low emphasizer. Most of the previous studies developed different clustering trials and chose the clustering trial that had the maximum number of significant indicators.…”
Section: The Taxonomies Of Green Operations Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…According to the life-cycle assessment process, all organizations should investigate the environmental impact of their operations over all aspects of their operational processes, products, and materials (Bjørn & Hauschild, 2013;Boehme, Panero, Muñoz, Powers, & Valle, 2009;de Bakker, 2001;Joshi, 1999;Matthews & Small, 2000;Migdadi & Elzzqaibeh, 2018;Migdadi & Omari, 2019), so that CO 2 emissions should be reported for suppliers' practices, logistics processes, business travel, manufacturing, customers' practices, and the operation of offices and facilities.…”
Section: Literature Reviewmentioning
confidence: 99%